The Impact Of The Qris Government Program As A Payment System On The Development Of Msmes In 2024 In An Islamic Economic Perspective (Study on culinary UMKM business actors in Labuhan Ratu Bandar Lampung City) - Angelique, Pingkan; Bahtiar, Muhammad Yusuf; Supriyaningsih, Okta (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to assess the impact of the implementation of the Quick Response Code Indonesian Standard (QRIS) payment system on the development of culinary SMEs in Labuhan Ratu, Bandar Lampung City, in the perspective of Islamic economics. By using a qualitative approach, primary data obtained through in-depth interviews with owners of culinary SMEs that have used QRIS. The results showed that QRIS has a positive impact on increasing transactions and ease of market access. In addition, the use of QRIS allows for more transparent financial management. However, challenges related to administrative costs and understanding of digital technology are still obstacles for some business owners. From the perspective of Islamic economics, QRIS is in line with the principles of fairness and transparency in transactions. This research contributes to the understanding of how the digitalization of payments can support the development of MSMEs by taking into account the principles of Islamic economics.